A Metal–Insulator Transition of the Buried MnO2 Monolayer in Complex Oxide Heterostructure. Issue 41 (29th August 2016) - Liu, Heng‐Jui; Lin, Jheng‐Cyuan; Fang, Yue‐Wen; Wang, Jing‐Ching; Huang, Bo‐Chao; Gao, Xiang; Huang, Rong; Dean, Philip R.; Hatton, Peter D.; Chin, Yi‐Ying; Lin, Hong‐Ji; Chen, Chien‐Te; et al.
Abstract : A novel artificially created MnO2 monolayer system is demonstrated in atomically controlled epitaxial perovskite heterostructures. With careful design of different electrostatic boundary conditions, a magnetic transition as well as a metal–insulator transition of the MnO2 monolayer is unveiled, providing a fundamental understanding of dimensionality‐confined strongly correlated electron systems and a direction to design new electronic devices.